PENGARUH VIRAL MARKETING DAN REVIEW ONLINE BAGI BISNIS UMKM TERHADAP KEPUTUSAN PEMBELIAN PENGGUNA TIKTOK (Studi Kasus Pada Bakso Cak Pitung Sidoarjo): Pengaruh Viral Marketing Dan Review Online Bagi Bisnis Umkm Terhadap Keputusan Pembelian Pengguna Tiktok (Studi Kasus Pada Bakso Cak Pitung Sidoarjo) - Adeta fajar mulya; Iik Claudia Firmandah; Novita Ayu Anggraini; Laily Muzdalifah (Universitas Nahdlatul Ulama Sidoarjo, 2023)
The purpose of this study was to identify the influence of viral marketing and online reviews on purchasing decisions for Bakso Pitung Sidoarjo. This research method uses a quantitative approach with descriptive analysis. The sampling technique used an accidental sampling technique with a total of 100 respondents using a Likert scale. Respondents to this study were users of the Tiktok application and also consumers of cak pitung meatballs. This research instrument has met the criteria of validity and reliability. Data processing using SPSS software version 26 and using multiple linear regression. Based on the research results, it is known that the viral marketing variable (X1) has a partially significant effect on purchasing decisions (Y). The online consumer review variable (X2) has a partially significant effect on the purchase decision variable (Y)